2021
DOI: 10.1007/s00259-021-05206-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ablation margins of FDG-avid liver tumors during PET/CT-guided thermal ablation procedures: a retrospective study

Abstract: Background To retrospectively assess liver tumor ablation margins using intraprocedural PET/CT images from FDG PET/CTguided microwave or cryoablation procedures and to correlate minimum margin measurements with local progression outcomes. Methods Fifty-six patients (ages 36 to 85, median 62; 32 females) with 77 FDG-avid liver tumors underwent 60 FDG PET/CT guided, percutaneous microwave, or cryoablation procedures. Single breath-hold PET/CT images were used for intraprocedural assessment of the tumor ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this study, we focused on the critical role of accurate registration in predicting residual tumor and analyzing AM, with a specific emphasis on addressing registration errors arising from tumor contraction (Tani et al 2016, Casadaban et al 2021. To tackle this issue, we introduced a tumor contraction model that utilizes the mean MEAV to calculate and adjust tumor volume following primary non-rigid registration.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the critical role of accurate registration in predicting residual tumor and analyzing AM, with a specific emphasis on addressing registration errors arising from tumor contraction (Tani et al 2016, Casadaban et al 2021. To tackle this issue, we introduced a tumor contraction model that utilizes the mean MEAV to calculate and adjust tumor volume following primary non-rigid registration.…”
Section: Discussionmentioning
confidence: 99%
“…The 2D assessment is time-consuming, and most importantly, cannot reliably discriminate between tumors that will eventually progress versus those that will not [13]. Several methods have been described regarding the assessment of the ablation zone after TA of liver tumors [30][31][32][33][34][35][36][37][38][39][40][41]. Assessing minimal margin in all anatomical planes is desirable and can be accomplished by the use of 3D models [13,34,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing minimal margin in all anatomical planes is desirable and can be accomplished by the use of 3D models [13,34,[36][37][38]. It has been shown that multiplanar, stereotactic volumetric assessments can provide more reliable measurements than the 2D method [13,40,42,43], that is prone to error independently of the interventional radiologist's expertise in percutaneous tumor ablation [43]. However, both 2D and 3D methods rely on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For biopsy-proven tumor-negative AZs, the MM size and SUV ratio were predictive surrogate imaging biomarkers of LTP [ 21 ]. Volumetric assessment of the MM has been used as an intraprocedural tool for ablation success [ 15 ] and a MM of 5 mm in a PET/CT ablation series correlated well with LTP [ 32 ]. In the current study, because of the imprecise portrayal of the tumor contour and edges, the theoretical 5- and 10-mm margins could not be defined in 32.1% of CLMs using CT alone.…”
Section: Discussionmentioning
confidence: 99%